Steel sheet and method for manufacturing same

By controlling the chemical composition and metal structure of the steel plate and combining the processing of multiple processes, the problem that high-strength steel plates in the prior art is difficult to achieve excellent bending and low-temperature LME resistance, and tensile strength above 1470MPa and significantly improved LME resistance are achieved.

CN119790176APending Publication Date: 2025-04-08NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380062200.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to provide large steel plates with tensile strength of more than 1470 MPa, excellent bending and low temperature liquid metal embrittlement (LME) resistance, especially in the assembly and installation of automotive parts, LME cracking is prone to occur.

Method used

By controlling the chemical composition and metal structure of the base material steel plate, it specifically includes specifying the volume ratio of the metal structure in a specific position in the cross-section in the thickness direction and in the surface area, and preparing the steel plate through multiple processes such as heating, hot rolling, coiling, cold rolling, annealing and cooling, etc., to ensure the high strength and LME resistance of the steel plate.

Benefits of technology

The tensile strength of the steel plate above 1470MPa, excellent bending properties and significantly improved low temperature LME resistance are achieved, effectively avoiding the LME cracking problem during spot welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005287002930000221
    Figure BDA0005287002930000221
  • Figure BDA0005287002930000231
    Figure BDA0005287002930000231
  • Figure BDA0005287002930000241
    Figure BDA0005287002930000241
Patent Text Reader

Abstract

This steel sheet is provided with: a base steel sheet having a prescribed chemical composition; and a zinc plating layer formed on the surface of the base steel sheet. T is the thickness of the base steel sheet. The metallographic structure at a t / 4 position, which is a t / 4 position from the surface in a cross-section in the thickness direction of the base steel plate, contains, in volume fraction, 85% or more of tempered martensite, 7% or more of retained austenite, and 0-8% of one or more elements selected from ferrite, pearlite, bainite, and primary martensite; the metal structure in a surface layer region, which is a region from the surface to a position of 50 [mu] m in the thickness-direction cross-section of the sheet, contains 30% or more by volume of bainite, with the remainder being one or more elements selected from ferrite, pearlite, tempered martensite, primary martensite, and retained austenite. The diameter of the prior austenite crystal grains in the plate thickness direction is 10.0 [mu] m or less, and the tensile strength of the steel plate is 1470 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel plate and a method for manufacturing the same.

[0002] This application claims priority based on Japanese Patent Application No. 2022-143631 filed in Japan on September 9, 2022, the contents of which are incorporated herein by reference. Background Art

[0003] In today's highly differentiated industrial technology field, materials used in various technical fields are required to be special and high-performance. In particular, regarding automobile steel sheets, in order to reduce the weight of the vehicle body and improve fuel efficiency, the demand for thin-walled, high-formability, high-tensile cold-rolled steel sheets has increased significantly due to concerns about the global environment. Among automobile steel sheets, especially cold-rolled steel sheets used in vehicle body frame parts, high strength is required, and high formability is required for application expansion. If the characteristics required for automobile steel sheets are exemplified, the tensile strength (TS) is above 1470MPa and the bendability is excellent.

[0004] Furthermore, in recent years, in order to sufficiently ensure the corrosion resistance of vehicle bodies and parts, high-strength hot-dip galvanized steel sheets and high-strength alloyed hot-dip galvanized steel sheets having a zinc coating on the surface of the steel sheet have been used.

[0005] For example, Patent Document 1 discloses a hot-dip galvanized steel sheet and alloyed hot-dip galvanized steel sheet having a temperature of 980 MPa or higher and excellent in plating properties, balance between strength and ductility, workability in bendability and hole expansion, and delayed fracture resistance, and a method for manufacturing the same.

[0006] However, there are problems with high-strength hot-dip galvanized steel sheets and high-strength alloyed hot-dip galvanized steel sheets in automobile parts. That is, in the processes of assembling the automobile body and installing the parts, resistance spot welding is mainly used. The so-called resistance spot welding is a resistance welding that is performed by clamping the overlapping base materials with the front end of the electrode after the front end is appropriately shaped, and concentrating the current and pressure on a relatively small part to locally heat it. However, for the assembly of the vehicle body and / or parts, if the galvanized steel sheet (hot-dip galvanized steel sheet, electrogalvanized steel sheet or alloyed hot-dip galvanized steel sheet) is subjected to resistance spot welding, cracks called molten metal embrittlement (Liquid Metal Embrittlement: LME) cracks may occur in the spot welds. LME cracks are caused by the heat generated during resistance spot welding, which melts the zinc in the zinc coating, and the molten zinc penetrates into the crystal grain boundaries of the steel sheet structure of the weld, and tensile stress acts on this state, thereby causing cracks. The necessary conditions for cracking to occur are that molten zinc contacts the solid steel sheet during welding and tensile stress (strain) acts on this portion. The higher the strength of the steel sheet, the higher the sensitivity to LME cracking tends to be.

[0007] Patent Document 1 does not disclose a steel plate having a tensile strength of 1470 MPa or more, nor does it study a countermeasure against LME cracking.

[0008] In order to solve the above-mentioned problems, a technique for improving the LME resistance of a galvanized steel sheet during spot welding has been proposed.

[0009] For example, Patent Document 2 discloses a steel plate, in which, in the cross-sectional structure cut along the width direction orthogonal to the rolling direction, the lath block diameter in the first depth region of 1 to 10 μm from the surface, the lath block diameter in the second depth region of 10 to 60 μm from the surface, and the lath block diameter in the third depth region of 60 μm to 1 / 4 of the plate thickness are respectively specified.

[0010] Patent document 2 shows the following: by making a three-layer structure in which the diameter of the plate block is controlled by tilting from the surface layer of the plate thickness toward the center layer of the plate thickness, the diameter of the plate block is large when it is deformed even during spot welding, so that the soft layer (the second layer) bears the strain, and it becomes possible to suppress the excessive increase of the strain in the outermost layer (the first layer), thereby making it possible to suppress the occurrence of spot welding LME cracks.

[0011] In Patent Document 2, it is believed that a certain effect of improving LME resistance can be obtained for LME cracking generated at a position heated to a high temperature, such as the contact surface of overlapping steel plates (sometimes referred to as high-temperature LME cracking). However, the inventors of the present invention have found out from the results of their research that, with the diversification of spot welding conditions in recent years, not only high-temperature LME cracking, for which countermeasures have been studied in the past, but also LME cracking (sometimes referred to as low-temperature LME cracking) may occur at the shoulder of the outermost surface of the steel plate in contact with the energized electrode, even if it is heated only to a temperature below the A1 point. It is known that as a countermeasure for low-temperature LME cracking, a countermeasure other than the high-temperature LME cracking countermeasure becomes necessary. In Patent Document 2, no countermeasure for such low-temperature LME cracking is studied.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: International Publication No. 2016 / 111275

[0015] Patent Document 2: International Publication No. 2021 / 251276 Summary of the invention

[0016] Problems to be solved by the invention

[0017] As described above, conventionally, there has been no disclosure of a steel sheet having a high strength of 1470 MPa or more and excellent bendability and low-temperature LME resistance.

[0018] Therefore, an object of the present invention is to provide a steel plate having a high strength of 1470 MPa or more and excellent bendability and low-temperature LME resistance, and a method for producing the same.

[0019] Means for solving problems

[0020] The inventors of the present invention have studied methods for improving strength, bendability and low temperature LME properties. As a result, they have found that it is effective to control the metal structure at the position t / 4, which is t / 4 from the surface of the base steel plate when the plate thickness of the base steel plate is set to t, and the metal structure in the range from the surface to the position of 50 μm, which is the surface layer region, respectively, based on the control of the chemical composition.

[0021] The present invention has been made based on the above-mentioned knowledge. The gist of the present invention is as follows.

[0022] [1] A steel sheet according to one embodiment of the present invention comprises: a base steel sheet; and a zinc plating layer formed on a surface of the base steel sheet, wherein the base steel sheet has the following chemical composition: in terms of mass %, C: 0.180% to 0.400%, Si: 0.050% to 1.000%, Mn: 2.00% to 4.00%, Al: 0.10% to 2.00%, Ti: 0.010% to 0.200%, B: 0.0010% to 0.0100%, N: 0.0010% to 0.0100%, P: 0% to 0.0400%, S: 0% to 0.0100%, O: 0% to 0.0060%, Cr: 0% to 0.50%, Ni: 0% to 1.00%, Cu: 0% to 1.00%, Mo: 0% to 0.500%, Nb: 0 %~0.200%, V: 0%~0.500%, W: 0%~0.100%, Ta: 0%~0.100%, Sn: 0%~0.050%, Co: 0%~0.500%, As: 0%~0.050%, Sb: 0%~ 0.050%, Mg: 0% to 0.050%, Ca: 0% to 0.040%, REM: 0% to 0.050%, Zr: 0% to 0.050%, Bi: 0% to 0.050%, Sr: 0% to 0.050% and the remainder: Fe and impurities, when the plate thickness of the above-mentioned base steel plate is set to t, the metal structure at the position t / 4 of the cross section in the plate thickness direction of the above-mentioned base steel plate at a distance of t / 4 from the above-mentioned surface, that is, the metal structure comprises, by volume percentage, tempered martensite: 85% or more, retained austenite: 7% or less The above-mentioned steel plate has a surface area of ​​50 μm from the surface to the top, and a metal structure of 30% or more bainite, and the remainder is ferrite, pearlite, tempered martensite, fresh martensite and retained austenite. In the surface area, the diameter of the original austenite grains in the thickness direction of the steel plate is less than 10.0 μm, and the tensile strength of the steel plate is greater than 1470 MPa.

[0023] [2] The steel sheet according to [1], wherein when the Al content in atomic % is set to "Al", the N content is set to "N", and the Ti content is set to "Ti", the formula (1) can also be satisfied.

[0024] 《Al》≥《N》-0.5×《Ti》 (1)

[0025] [3] The steel sheet according to [1] or [2], wherein the zinc coating layer may be a hot-dip galvanized layer.

[0026] [4] The steel sheet according to [1] or [2], wherein the zinc coating layer may be an alloyed hot-dip galvannealing layer.

[0027] [5] A method for manufacturing a steel plate according to another embodiment of the present invention comprises the following steps: a heating step, in which a slab is heated in such a manner that a heating temperature T in K satisfies the formula (2) when the Al content in mass % is set to [Al] and the N content is set to [N]; a hot rolling step in which the slab after the heating step is hot-rolled to obtain a steel plate; a coiling step in which the steel plate is cooled at an average cooling rate of 20°C / s or more to a coiling temperature of 500°C or less and coiled at the coiling temperature; a cold rolling step in which the steel plate after the coiling step is pickled as required and then rolled at a temperature of 20% or less. The steel sheet is subjected to cold rolling at a cumulative reduction rate of 100°C; an annealing step, wherein the steel sheet is heated to an annealing temperature of Ac3 point to 900°C in an atmosphere with an oxygen potential of -1.50 or higher, and maintained at the annealing temperature for 10 seconds to 600 seconds; a first cooling step of cooling the steel sheet after the annealing step to a first temperature range of Ms point -100°C to Bs point at an average cooling rate of 20°C / second or higher; a holding step of maintaining the steel sheet in the first temperature range for 60 seconds to 600 seconds; and a second cooling step of cooling the steel sheet after the holding step to a second temperature range of 250°C to 150°C at an average cooling rate of 20°C / second or higher.

[0028] log 10 ([Al]×[N])≤-9730 / T+3.36 (2)

[0029] Effects of the Invention

[0030] According to the above aspects of the present invention, it is possible to provide a steel sheet having a high strength of 1470 MPa or more and excellent in bendability and low-temperature LME resistance, and a method for producing the same. DETAILED DESCRIPTION

[0031] A steel plate according to one embodiment of the present invention (the steel plate according to the present embodiment) comprises: a base steel plate having a predetermined chemical composition; and a zinc plating layer formed on the surface of the base steel plate, wherein the base steel plate has a predetermined metal structure in a surface region, i.e., a position t / 4 away from the surface in a cross section in a plate thickness direction and a range from the surface to a position of 50 μm in the cross section in the plate thickness direction, wherein the diameter of prior austenite grains in the plate thickness direction is less than 10.0 μm, and the tensile strength of the steel plate is greater than 1470 MPa.

[0032] The following will explain each one separately.

[0033] [Base Steel Plate]

[0034] <Chemical Composition>

[0035] The chemical composition of the base steel plate of the steel plate according to the present embodiment will be described. "%" of the content of each element means "mass %" unless otherwise specified.

[0036] C: 0.180%~0.400%

[0037] C (carbon) is an element necessary for ensuring the strength of the steel sheet. By setting the C content to 0.180% or more, a desired high strength can be obtained. The C content is preferably 0.200% or more, and more preferably 0.220% or more.

[0038] On the other hand, in order to ensure workability and weldability, the C content is set to 0.400% or less. The C content is preferably 0.380% or less, and more preferably 0.360% or less.

[0039] Si: 0.050%~1.000%

[0040] Si (silicon) is an element effective for suppressing the formation of iron carbides in austenite with increased C concentration and obtaining stable retained austenite even at room temperature. In order to obtain this effect, the Si content is set to 0.050% or more.

[0041] On the other hand, in order to ensure the weldability of the steel sheet, the Si content is set to 1.000% or less. The Si content is preferably 0.900% or less, and more preferably 0.800% or less.

[0042] Mn: 2.00%~4.00%

[0043] Mn (manganese) is a strong austenite stabilizing element and an element effective for increasing the strength of the steel sheet. In order to obtain these effects, the Mn content is set to 2.00% or more. The Mn content is preferably 2.20% or more, and more preferably 2.40% or more.

[0044] On the other hand, if the Mn content is high, weldability and low-temperature toughness decrease. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.60% or less, and more preferably 3.20% or less.

[0045] Al: 0.10%~2.00%

[0046] Al (aluminum) is an element used for deoxidation of steel, and is an element effective for suppressing the formation of iron carbides and obtaining retained austenite, similarly to Si.

[0047] In addition, in the steel plate of the present embodiment, Al is an element that precipitates as AlN and contributes to the refinement of the structure. In order to obtain the above-mentioned effect, the Al content (total Al content) is set to 0.10% or more. In addition, as described later, the Al content is preferably set to a range that satisfies the formula (1) in terms of atomic % in relation to the Ti content and the N content.

[0048] On the other hand, even if Al is contained excessively, the effect is saturated, not only the cost is increased, but also the phase transformation temperature of the steel increases, thereby increasing the load during hot rolling. Therefore, the Al content is set to 2.00% or less. The Al content is preferably 1.50% or less, and more preferably 1.20% or less.

[0049] Ti: 0.010%~0.200%

[0050] Ti (titanium) is an element effective for fixing N by becoming TiN, thereby securing solid solution B that contributes to improving hardenability. In order to obtain this effect, the Ti content is set to 0.010% or more.

[0051] On the other hand, if the Ti content exceeds 0.200%, coarse carbonitrides may precipitate, and the formability may be reduced. Therefore, the Ti content is set to 0.200% or less. The Ti content is preferably 0.180% or less, and more preferably 0.160% or less.

[0052] Furthermore, if the Ti content exceeds a predetermined ratio relative to the Al content, the precipitation of AlN is inhibited by the excessive precipitation of TiN. Therefore, as described later, the Ti content is preferably set to a range that satisfies the formula (1) in terms of atomic % in relation to the Al content and the N content.

[0053] B: 0.0010%~0.0100%

[0054] Boron (B) is an element that segregates at austenite grain boundaries during welding to strengthen the crystal grain boundaries and contribute to the improvement of resistance to molten metal embrittlement cracking. In addition, it is an element that improves the hardenability of steel and contributes to the high strength of the steel plate.

[0055] In order to obtain the above-mentioned effect, the B content is set to 0.0010% or more, preferably 0.0015% or more, and more preferably 0.0020% or more.

[0056] On the other hand, if the B content exceeds 0.0100%, carbides and nitrides are generated, the above-mentioned effects are saturated, and hot workability is reduced. Therefore, the B content is set to 0.0100% or less. The B content is preferably 0.0080% or less, more preferably 0.0050% or less, and further preferably 0.0030% or less.

[0057] N: 0.0010%~0.0100%

[0058] N (nitrogen) is an element that combines with Al to precipitate as AlN and contributes to the refinement of the structure. In order to obtain this effect, the N content is set to 0.0010% or more. The N content is preferably 0.0020% or more.

[0059] On the other hand, if the N content exceeds 0.0100%, coarse nitrides are formed in the steel, and the bendability and hole expandability are deteriorated. Therefore, the N content is set to 0.0100% or less. The N content is preferably 0.0080% or less, and more preferably 0.0060% or less.

[0060] P: 0%~0.0400%

[0061] P (phosphorus) is a solid solution strengthening element and is an element effective for increasing the strength of the steel plate, but excessive inclusion deteriorates weldability and toughness. Therefore, the P content is set to 0.0400% or less. The P content is preferably 0.0350% or less, 0.0300% or less, or 0.0200% or less. The P content may also be 0%, but in order to extremely reduce the P content, the cost of removing P becomes high. Therefore, from the perspective of economic efficiency, the P content may also be set to 0.0010% or more.

[0062] S: 0%~0.0100%

[0063] S (sulfur) is an element contained as an impurity, and is an element that forms MnS in steel and deteriorates toughness and hole expansion. Therefore, as a range in which the deterioration of toughness and hole expansion is not significant, the S content is set to 0.0100% or less. The S content is preferably 0.0050% or less, 0.0040% or less, or 0.0030% or less. The S content may also be 0%, but in order to extremely reduce the S content, the desulfurization cost becomes high. Therefore, from the perspective of economy, the S content may also be set to 0.0001% or more or 0.0010% or more.

[0064] O: 0%~0.0060%

[0065] O (oxygen) is an element contained as an impurity. If its content exceeds 0.0060%, it forms coarse oxides in steel and deteriorates bendability and hole expansion. Therefore, the O content is set to 0.0060% or less. The O content is preferably 0.0050% or less, and more preferably 0.0040% or less. The O content may be 0%, but from the viewpoint of manufacturing cost, the O content may be set to 0.0001% or more.

[0066] The basic chemical composition of the steel sheet of this embodiment includes the above-mentioned elements (basic elements), and the remainder includes Fe and impurities. Here, the "impurities" refer to components mixed in the steel sheet due to various factors such as raw materials such as ores and wastes and the manufacturing process when the steel sheet is manufactured industrially, and are components that are allowed within the range that does not adversely affect the present invention.

[0067] However, the steel plate may contain the following elements (optional elements) as needed to replace part of Fe. These elements may not necessarily be contained, so the lower limit is 0%. In addition, the following elements may also be mixed from scraps of raw materials, but if the content is below the upper limit value described later, it may be intentionally contained in the steel plate or unintentionally contained in the steel plate. For example, the following elements may be contained in the steel plate by being contained in scraps of raw materials of the steel plate.

[0068] Cr: 0%~0.50%

[0069] Ni: 0%~1.00%

[0070] Cu: 0%~1.00%

[0071] Cr (chromium), Ni (nickel) and Cu (copper) are all elements that contribute to improving strength. Therefore, one or more selected from these elements may be contained as required. In the case of obtaining the above-mentioned effect, the content of one or more selected from Cr, Ni and Cu is preferably 0.01% or more, more preferably 0.10% or more.

[0072] On the other hand, a Cr content exceeding 0.50%, a Ni content exceeding 1.00%, or a Cu content exceeding 1.00% may reduce pickling properties, weldability, and hot workability. Therefore, the Cr content is set to 0.50% or less, the Ni content is set to 1.00% or less, and the Cu content is set to 1.00% or less. The Cr content may also be 0.40% or less, 0.30% or less, or 0.10% or less. The Ni content may also be 0.80% or less, 0.60% or less, or 0.20% or less. The Cu content may also be 0.80% or less, 0.60% or less, or 0.20% or less.

[0073] Mo: 0%~0.500%

[0074] Mo (molybdenum) is an element that improves the hardenability of steel and contributes to the improvement of strength, similarly to Mn. Therefore, Mo may be contained as required. In the case of obtaining the above-mentioned effect, the Mo content is preferably 0.010% or more, and more preferably 0.100% or more.

[0075] On the other hand, if the Mo content exceeds 0.500%, hot workability may be reduced and productivity may be reduced. Therefore, the Mo content is set to 0.500% or less. The Mo content is preferably 0.400% or less, more preferably 0.300% or less, and further preferably 0.100% or less.

[0076] Nb: 0%~0.200%

[0077] V: 0%~0.500%

[0078] Nb (niobium) and V (vanadium) are elements that contribute to improving the strength of the steel sheet through precipitation strengthening, fine grain strengthening due to grain growth inhibition, and dislocation strengthening due to recrystallization inhibition. Therefore, one or more selected from these elements may be contained as required. In the case of obtaining the above-mentioned effects, it is preferred that the steel sheet contain one or two of 0.001% or more of Nb and 0.001% or more of V.

[0079] On the other hand, a Nb content exceeding 0.200% or a V content exceeding 0.500% may precipitate coarse carbonitrides and reduce formability. Therefore, the Nb content is set to 0.200% or less, and the V content is set to 0.500% or less. The Nb content is preferably 0.180% or less, more preferably 0.150% or less, and further preferably 0.100% or less. The V content is preferably 0.400% or less, more preferably 0.300% or less, and further preferably 0.100% or less.

[0080] W: 0%~0.100%

[0081] Ta: 0%~0.100%

[0082] Sn: 0%~0.050%

[0083] Co: 0%~0.500%

[0084] As: 0%~0.050%

[0085] W (tungsten), Ta (tantalum), Sn (tin), Co (cobalt) and As (arsenic) are elements that contribute to improving the strength of the steel sheet by suppressing precipitation strengthening and coarsening of grains. Therefore, these elements may also be contained. In order to obtain the effect, it is preferred to contain one or more of these elements, set the W content to 0.001% or more, set the Ta content to 0.001% or more, set the Sn content to 0.001% or more, set the Co content to 0.001% or more, and set the As content to 0.001% or more.

[0086] On the other hand, if these elements are contained in large amounts, various properties of the steel sheet may be impaired. Therefore, the W content is set to 0.100% or less, the Ta content is set to 0.100% or less, the Sn content is set to 0.050% or less, the Co content is set to 0.500% or less, and the As content is set to 0.050% or less. The W content is preferably 0.080% or less, more preferably 0.050% or less, and further preferably 0.030% or less. The Ta content is preferably 0.080% or less, more preferably 0.050% or less, and further preferably 0.030% or less. The Sn content is preferably 0.040% or less, more preferably 0.030% or less, and further preferably 0.010% or less. The Co content is preferably 0.400% or less, more preferably 0.300% or less, and further preferably 0.100% or less. The As content is preferably 0.040% or less, more preferably 0.030% or less, and further preferably 0.010% or less.

[0087] Sb: 0%~0.050%

[0088] Mg: 0%~0.050%

[0089] Ca: 0%~0.040%

[0090] REM: 0%~0.050%

[0091] Zr: 0%~0.050%

[0092] Bi: 0%~0.050%

[0093] Sr: 0%~0.050%

[0094] Sb (antimony), Mg (magnesium), Ca (calcium), REM (Rare Earth Metal), Zr (zirconium), Bi (bismuth) and Sr (strontium) are all elements that contribute to improving formability. Therefore, one or more selected from these elements may be contained as needed. In the case where the above-mentioned effects are desired, it is preferred to contain one or more selected from Sb, Mg, Ca, REM, Zr, Bi and Sr, and set the content of each to 0.001% or more. The content of each element is more preferably 0.002% or more.

[0095] On the other hand, a content of Sb, Mg, REM, Zr, Bi or Sr exceeding 0.050% or a content of Ca exceeding 0.040% may reduce pickling properties, weldability and hot workability. Therefore, the contents of Sb, Mg, REM, Zr, Bi and Sr are all set to 0.050% or less, and the content of Ca is set to 0.040% or less. The contents of Sb, Mg, Ca, REM, Zr, Bi and Sr are preferably 0.035% or less, 0.030% or less or 0.010% or less.

[0096] In the present embodiment, REM refers to rare earth elements, which is a general term for a total of 17 elements including Sc, Y, and lanthanoid elements, and the REM content is the total content of these elements.

[0097] As described above, the chemical composition of the base steel plate of the steel plate of the present embodiment includes the basic elements and the balance includes Fe and impurities, or includes the basic elements and further includes one or more of the optional elements and the balance includes Fe and impurities.

[0098] In the steel sheet of the present embodiment, the crystal grain size is made fine by AlN precipitated during continuous annealing. If the Al content is small relative to the N content that is not consumed as TiN and remains, AlN may not be fully formed. Therefore, when the Al content in atomic % is set to "Al", the N content is set to "N", and the Ti content is set to "Ti", it is preferable to satisfy formula (1).

[0099] 《Al》≥《N》-0.5×《Ti》 (1)

[0100] The chemical composition of the base steel plate of the steel plate of the present embodiment can be measured by a general method. For example, it can be measured according to JIS G 1201: 2014 and using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) for cuttings. In this case, the chemical composition is the average content in the entire plate thickness. C and S that cannot be measured by ICP-AES can be measured by combustion-infrared absorption method, N can be measured by inert gas melting-thermal conductivity method, and O can be measured by inert gas melting-non-dispersive infrared absorption method.

[0101] The analysis sample was collected so as to obtain the average chemical composition of the entire thickness of the base steel plate as described in JIS G 0417: 1999. Specifically, the analysis sample was collected from a position 1 / 4 of the plate thickness in the plate thickness direction from the surface, avoiding the width direction ends of the base steel plate.

[0102] In the above method, the content of the element is measured in mass %. The content in atomic % is calculated by converting the content in mass % using the following conversion formula.

[0103] 《Al》=([Al] / 27) / A

[0104] 《N》=([N] / 14) / A

[0105] 《Ti》=([Ti] / 47.9) / A

[0106] In the above formula, [element symbol] represents the amount of each element contained in the steel plate (unit: mass %), and A is a value obtained from the content of each element by the following formula.

[0107] A=[Fe] / 55.8+[C] / 12+[Si] / 28.1+[Mn] / 54.9+[Al] / 27+[Ti] / 47.9+[B] / 10.8+[N] / 14+[ P] / 31+[S] / 32.1+[O] / 16+[Cr] / 52+[Ni] / 58.7+[Cu] / 63.5+[Mo] / 95.9+[Nb] / 92.9+[V] / 50.9+[W] / 183.8+[Ta] / 180.9+[Sn] / 118.7+[Co] / 63.6+[As] / 74.9+[Sb] / 121.8+[Mg] / 2 4.3+[Ca] / 40.1+[Y] / 88.9+[La] / 138.9+[Ce] / 140.1+[Zr] / 91.2+[Bi] / 209+[Sr] / 87.6.

[0108] <Metallic Structure>

[0109] In the steel plate of the present embodiment, the metal structure at the position t / 4 where the distance from the surface of the base steel plate (that is, when coated, the surface of the steel plate of the present embodiment after the coating is removed) is t / 4 in the cross section in the thickness direction when the thickness of the base steel plate is set to t, and the metal structure in the range from the surface to the position of 50 μm, that is, the surface region.

[0110] Hereinafter, the fraction of each phase of the metal structure is the volume fraction.

[0111] (Metal structure at position t / 4)

[0112] First, the metal structure at the position t / 4 will be described.

[0113] Tempered martensite: more than 85%

[0114] In the steel sheet of the present embodiment, in order to ensure a tensile strength of 1470 MPa or more, the volume fraction of tempered martensite is set to 85% or more. When the volume fraction of tempered martensite is less than 85%, sufficient tensile strength cannot be ensured. When the volume fraction of tempered martensite exceeds 93%, sufficient volume fraction of retained austenite cannot be ensured, so the volume fraction of tempered martensite is 93% or less.

[0115] From the viewpoint of contributing to high strength, fresh martensite is also effective. However, fresh martensite is a brittle structure and has poor formability. Therefore, in the steel sheet of the present embodiment, tempered martensite is used as the main structure.

[0116] Retained austenite: more than 7%

[0117] Retained austenite is a structure that improves the elongation of the steel sheet by the TRIP effect of transformation into martensite through work-induced transformation during deformation of the steel sheet. Therefore, the volume fraction of retained austenite is set to 7% or more.

[0118] The higher the volume fraction of retained austenite is, the higher the elongation of the steel sheet is. However, in order to obtain a large amount of retained austenite, it is necessary to contain a large amount of alloy elements such as C. Therefore, the volume fraction of retained austenite is set to 15% or less.

[0119] One or more selected from ferrite, pearlite, bainite, and fresh martensite: 0% to 8%

[0120] The remainder other than tempered martensite and retained austenite may include one or more selected from ferrite, pearlite, bainite and fresh martensite. In order to ensure the prescribed volume ratio of tempered martensite and retained austenite, the volume ratio of the remainder is 8% or less. The volume ratio of the remainder is preferably 5% or less, more preferably 3% or less. The volume ratio of the remainder may also be 0%.

[0121] The volume fraction of each structure (phase) at the t / 4 position is determined by the following procedure.

[0122] That is, regarding the volume ratio of ferrite, pearlite, bainite, primary martensite, and tempered martensite, a test piece is collected from an arbitrary position relative to the rolling direction of the steel plate and a position in the center relative to the width direction, and a longitudinal section parallel to the rolling direction (i.e., a section parallel to the rolling direction and parallel to the thickness direction) is ground, and the metal structure that appears by nitric acid etching is observed using SEM at a position 1 / 4 of the plate thickness t from the surface in the plate thickness direction. In the SEM observation, 5 fields of view of 30 μm in the plate thickness direction and 50 μm in the rolling direction are observed at a magnification of 3000 times, in a manner that the position 1 / 4 of the plate thickness t from the surface in the plate thickness direction is in the center, and the area ratio of each organization is measured from the observed image, and the average value is calculated. Since there is no organizational change in the direction perpendicular to the rolling direction (the width direction of the steel plate), the area ratio of the longitudinal section parallel to the rolling direction is equal to the volume ratio, so the area ratio obtained in the organizational observation is taken as the respective volume ratios.

[0123] When measuring the area ratio of each structure, the region where the lower structure does not appear and the brightness is low is set as ferrite. In addition, the region of the layered structure of ferrite and cementite is set as pearlite. In addition, the region where the lower structure does not appear and the brightness is high is set as primary martensite or retained austenite. In addition, the region where the lower structure appears is set as tempered martensite or bainite.

[0124] Bainite and tempered martensite are distinguished by further careful observation of the carbides within the grains.

[0125] Specifically, tempered martensite is composed of martensite laths and cementite generated inside the laths. At this time, the crystal orientation relationship of martensite laths and cementite exists more than two kinds, so the cementite constituting tempered martensite has multiple variants. On the other hand, bainite is classified into upper bainite and lower bainite. Upper bainite is composed of lath-shaped bainitic ferrite and cementite generated at the lath interface, so it is easy to distinguish from tempered martensite. Lower bainite is composed of lath-shaped bainitic ferrite and cementite generated inside the lath. At this time, the crystal orientation relationship of bainitic ferrite and cementite is different from that of tempered martensite, which is 1 kind, and the cementite constituting lower bainite has the same variant. Therefore, lower bainite is distinguished from tempered martensite based on the variant of cementite.

[0126] On the other hand, fresh martensite and retained austenite are not clearly distinguished in SEM observation. Therefore, the volume fraction of martensite is calculated by subtracting the volume fraction of retained austenite calculated by the method described below from the volume fraction of a structure determined to be martensite or retained austenite.

[0127] Regarding the volume fraction of retained austenite, a test piece was collected from an arbitrary position relative to the rolling direction of the steel plate and at a central position relative to the width direction, and the rolled surface was chemically polished from the surface of the steel plate to a position 1 / 4 of the plate thickness, and quantified by the (200) and (210) area integral intensities of ferrite and the (200), (220) and (311) area integral intensities of austenite obtained using MoKα rays.

[0128] (Metallic structure in the surface area)

[0129] Next, the metal structure in the surface layer region will be described.

[0130] Bainite: 30% by volume or more

[0131] By setting the surface region to a soft structure, the bendability is improved. However, if the difference between the hardness of the surface region and the hardness of the inside of the steel plate (for example, the t / 4 position) is too large, the strain is concentrated in the surface region, and the bendability may be reduced. Therefore, in the surface region, the volume fraction of bainite is set to 30% or more. The volume fraction of bainite is preferably 50% or more, and more preferably 70% or more. Bainite can also be 100%.

[0132] The remainder: at least one selected from ferrite, pearlite, tempered martensite, fresh martensite and retained austenite

[0133] The remainder other than bainite is one or more selected from the group consisting of ferrite, pearlite, tempered martensite, fresh martensite and retained austenite.

[0134] Among them, ferrite contributes to the improvement of bendability and also contributes to the improvement of LME resistance. Therefore, it is preferable that ferrite and bainite are contained so that the total volume ratio becomes 50% or more.

[0135] Diameter of prior austenite grains in the plate thickness direction: 10.0 μm or less

[0136] The inventors of the present invention studied LME cracking of a steel plate in which the metal structure at the t / 4 position and the surface region was controlled as described above, and found that the diffusion path of molten zinc, which is the cause of LME cracking, is the prior austenite grain boundary, and therefore LME cracking can be suppressed by reducing the diameter of the prior austenite grains in the plate thickness direction.

[0137] Therefore, in the steel plate of the present embodiment, the diameter of the prior austenite grains in the plate thickness direction is set to 10.0 μm or less in the surface layer region. By reducing the diameter of the prior austenite grains in this way, not only high-temperature LME cracking but also low-temperature LME cracking can be suppressed. If the diameter of the prior austenite grains in the plate thickness direction exceeds 10.0 μm, the diffusion of molten zinc is large, and low-temperature LME cracking becomes easy to occur.

[0138] The diameter of the prior austenite grains in the plate thickness direction is preferably 9.0 μm or less, more preferably 7.0 μm or less.

[0139] The volume ratio of each structure in the metal structure of the surface layer region can be measured by the same method as the measurement at the above-mentioned t / 4 position. However, regarding the observation range using SEM, the viewing field of 30 μm in the plate thickness direction and 50 μm in the rolling direction is set as three viewing fields in such a manner that the position 15 μm from the surface is in the center, and the viewing field of 30 μm in the plate thickness direction and 50 μm in the rolling direction is set as three viewing fields in such a manner that the position 35 μm from the surface is in the center.

[0140] In addition, the diameter of the prior austenite grains in the plate thickness direction was obtained by the following method.

[0141] The crystal orientation analysis (SEM-EBSD) using SEM and backscattered electrons in the cross section in the plate thickness direction is used to shoot a range of 30 μm to 50 μm from the surface. In the obtained image, a straight line is drawn from a position 30 μm from the surface in the plate thickness direction to a position 50 μm from the surface, and the number of original austenite grains contained in the straight line is counted. The diameter of the original austenite grain in the plate thickness direction is calculated by dividing the number of the obtained original austenite grains by 20 μm (measurement distance). The above measurement is performed at more than 5 locations in a direction perpendicular to the plate thickness direction, and the diameter of the original austenite grain in the plate thickness direction at each position is averaged as the diameter of the original austenite grain in the surface area in the plate thickness direction.

[0142] Here, regarding the original austenite grains, the crystal orientation data of BCC-iron is measured by SEM-EBSD. In the obtained BCC-iron crystal orientation map (MAP) data, the boundary with a crystal orientation difference of 15 degrees or more is set as the crystal grain boundary, and the crystal grain boundary of tempered martensite, primary martensite and bainite is judged. At this time, the area where the GAM value (Grain Average Misorientation) in the crystal surrounded by the above-mentioned grain boundary is greater than 0.5 degrees is judged as tempered martensite, primary martensite or bainite. The measurement interval (STEP) is set to 0.01μm~0.10μm, and 0.05μm can also be selected.

[0143] [Plating]

[0144] The steel sheet of this embodiment has a zinc coating. The zinc coating improves corrosion resistance. If there is a concern that a steel sheet for automobiles may be pierced due to corrosion, it is possible that even if the steel sheet is made high-strength, it cannot be thinned to a certain thickness or less. One of the purposes of increasing the strength of a steel sheet is to reduce the weight by thinning the wall, so even if a high-strength steel sheet is developed, if the corrosion resistance is low, the application area is limited. As a method for solving these problems, a zinc coating with high corrosion resistance is formed on the surface of the steel sheet.

[0145] The zinc coating may be a hot-dip galvanized layer or an alloyed hot-dip galvanized layer. The hot-dip galvanized layer is preferred from the perspective of cost, and the alloyed hot-dip galvanized layer is preferred from the perspective of obtaining excellent weldability and paintability because Fe is incorporated into the hot-dip galvanized layer through alloying treatment.

[0146] In addition, the zinc coating may be coated with an upper layer for the purpose of improving the coating property and weldability. In addition, in the cold-rolled steel sheet of the present embodiment, various treatments such as chromate treatment, phosphate treatment, lubricity improvement treatment, weldability improvement treatment, etc. may be performed on the hot-dip galvanized layer.

[0147] [characteristic]

[0148] Tensile strength: 1470MPa or more

[0149] In the steel sheet of the present embodiment, the tensile strength (TS) is 1470 MPa or more, which is strength that contributes to weight reduction of the automobile body.

[0150] The upper limit of the tensile strength is not limited. However, if the tensile strength is too high, the formability may be reduced. Therefore, the tensile strength may be set to 1600 MPa or less.

[0151] The tensile strength (TS) was determined by collecting a JIS No. 5 tensile test piece from a steel plate in a direction perpendicular to the rolling direction and performing a tensile test in accordance with JIS Z 2241:2011.

[0152] Furthermore, since the chemical composition and metal structure of the steel sheet according to the present embodiment are limited as described above, the steel sheet is excellent in bendability and low-temperature LME resistance.

[0153] As for the bending property, it is preferable that the maximum bending angle evaluated by the bending test according to the VDA standard is 90 degrees or more.

[0154] [Plate thickness]

[0155] The plate thickness of the steel plate of the present embodiment is not limited, but is preferably 1.0 mm to 3.0 mm from the viewpoint of achieving both weight reduction of the automobile body and improvement of collision safety.

[0156] [Manufacturing method]

[0157] Next, a preferred example of a method for manufacturing a steel plate according to the present embodiment is described. According to the manufacturing method, a steel plate according to the present embodiment can be obtained. However, the manufacturing method described below does not limit the scope of the steel plate according to the present embodiment. A steel plate that meets the above-mentioned necessary conditions is regarded as a steel plate according to the present embodiment regardless of its manufacturing method.

[0158] Specifically, the steel sheet of the present embodiment is obtained by a production method having the following steps.

[0159] (I) a heating step, wherein the heating temperature T in K satisfies log 0.0104 when the Al content in mass % is set to [Al] and the N content is set to [N] 10 The slab is heated in the manner of ([Al]×[N])≤-9730 / T+3.36;

[0160] (II) hot rolling the slab after the heating step to obtain a steel plate;

[0161] (III) a coiling step of cooling the steel sheet at an average cooling rate of 20° C. / s or more to a coiling temperature of 500° C. or less, and coiling the steel sheet at the coiling temperature;

[0162] (IV) a cold rolling step, wherein the steel sheet after the coiling step is pickled as necessary and then cold rolled at a cumulative reduction ratio of 20% or less;

[0163] (V) an annealing step of heating the steel sheet to an annealing temperature of Ac3 point to 900° C. in an atmosphere having an oxygen potential of −1.50 or higher, and maintaining the annealing temperature for 10 seconds to 600 seconds;

[0164] (VI) a first cooling step of cooling the steel sheet after the annealing step to a first temperature range of Ms point - 100°C to Bs point at an average cooling rate of 20°C / sec or more;

[0165] (VII) a step of maintaining the first temperature range for 60 seconds to 600 seconds; and

[0166] (VIII) A second cooling step of cooling the steel sheet after the holding step to a second temperature range of 250° C. to 150° C. at an average cooling rate of 20° C. / sec or more.

[0167] In order to obtain the steel plate of the present embodiment, it is necessary to make the metal structure into a needle-shaped structure through a hot rolling process and a coiling process, and anneal the steel plate with the needle-shaped structure under the conditions described below, so that the aspect ratio of the original austenite grains of the annealed steel plate is increased, the diameter of the original austenite grains in the plate thickness direction is reduced, and the metal structure at the t / 4 position and the metal structure of the surface area are controlled. They are obtained by a combination of multiple processes. That is, not only a single process is important, but also because the chemical composition and the conditions from the heating process to the second cooling process affect the conditions of other processes, it is also important to perform condition control in each process that also takes into account the conditions of other processes, and to perform overall control in a series of processes.

[0168] The Ac3 point is obtained by the following formula.

[0169] Ac3(℃)=910-203×[C] 1 / 2 +44.7×[Si]-30×[Mn]+700×[P]-20×[Cu]-15.2×[Ni]-11×[Cr]+31.5×[Mo]+400×[Ti]+104×[V]+120×[Al]

[0170] The Ms point refers to a temperature at which martensite starts to form during cooling after quenching. In the production method of the present embodiment, a value calculated by the following mathematical formula is regarded as the Ms point.

[0171] Ms(℃)=541-474×[C] / (1-Sα / 100)-15×[Si]-35×[Mn]-17×[Cr]-17×[Ni]+19×[Al]

[0172] The Bs point is a temperature at which bainite transformation starts during cooling after quenching. In the production method of the present embodiment, a value calculated by the following mathematical formula is regarded as the Bs point.

[0173] Bs(℃)=820-290×[C] / (1-Sα)-37×[Si]-90×[Mn]-65×[Cr]-50×[Ni]+70×[Al]

[0174] The [element symbol] contained in the calculation formula of the Ac3 point, Ms point, and Bs point represents the amount of each element contained in the steel plate (in mass %). In addition, the symbol Sα contained in the formula represents the ferrite fraction (in volume %) of the steel plate at the time when the heating for quenching is completed.

[0175] However, it is difficult to find the area ratio of ferrite in a steel plate being manufactured. Therefore, a steel plate that has undergone the same temperature history as the actual steel plate manufacturing process is prepared in advance to find the area ratio of ferrite in the center of the steel plate, and the area ratio of ferrite is used to calculate Ms and Bs. The ferrite fraction of a steel plate generally depends on the heating temperature for quenching. Therefore, when studying the cooling conditions, the manufacturing conditions of the process before cooling are first determined, and the steel plate is manufactured under the manufacturing conditions. By measuring its ferrite fraction, Sα can be determined.

[0176] <Heating process>

[0177] In the heating step, when the Al content in mass % is set to [Al] and the N content is set to [N], the slab is heated so that the heating temperature T in unit K satisfies the formula (2).

[0178] log 10 ([Al]×[N])≤-9730 / T+3.36 (2)

[0179] In the heating process, Al and N in the slab are made into a solid solution state. Therefore, it is necessary to heat to a temperature that satisfies the formula (2) that takes into account the solubility product of Al and N. If the formula (2) is not satisfied, the coarse AlN precipitated during casting remains, and the fine AlN cannot be precipitated during annealing. The coarse AlN precipitated during casting basically does not contribute to the refinement of the structure. The upper limit of the heating temperature in the heating process is not particularly limited, but from the perspective of the capacity and productivity of the heating equipment, the heating temperature is, for example, below 1350°C.

[0180] The method for producing the slab to be used in the heating step is not limited. It is sufficient as long as a steel slab having the above chemical composition is produced by melting, refining, and casting. For example, it can be produced by continuous casting, a thin slab continuous casting machine, etc.

[0181] <Hot rolling process>

[0182] In the hot rolling process, the slab after the heating process is hot rolled to form a steel sheet.

[0183] The hot rolling conditions preferably set the finishing temperature of the finishing rolling to 850°C or above. In the hot rolling process and the coiling process, the metal structure is made into a needle-shaped structure. However, if the finishing temperature of the finishing rolling is lower than 850°C, ferrite and / or pearlite with a small aspect ratio are generated, and the proportion of the needle-shaped structure (bainite, martensite) in the steel plate is reduced. From the perspective of productivity, the upper limit of the finishing temperature of the finishing rolling is, for example, below 1350°C.

[0184] <Coiling process>

[0185] In the coiling process, the steel sheet after the hot rolling process is cooled to a coiling temperature of 500°C or less at an average cooling rate of 20°C / s or more, and coiled at the coiling temperature. Thus, the structure of the steel sheet after the coiling process is made into a needle-like structure. By annealing the steel sheet having the needle-like structure under the conditions described below, the aspect ratio of the original austenite grains of the annealed steel sheet can be increased, and the diameter of the original austenite grains in the plate thickness direction can be reduced.

[0186] If the average cooling rate until the coiling temperature is lower than 20°C / sec, or the coiling temperature exceeds 500°C, ferrite and / or pearlite with a small aspect ratio are generated, and the proportion of the acicular structure in the steel plate decreases. The average cooling rate until the coiling temperature is, for example, 200°C / sec or lower. From the perspective of productivity, the coiling temperature is, for example, 20°C or higher.

[0187] <Cold rolling process>

[0188] In the cold rolling process, the steel plate after the coiling process is pickled as needed and then cold rolled. When the steel plate is cold rolled, the cold rolling rate (cumulative reduction rate) is set to 20% or less. If the cold rolling rate is set to more than 20%, a large number of dislocations are contained in the steel plate after the cold rolling process. Since the steel plate is heated for annealing, the dislocations promote the recrystallization of the structure of the steel plate, and the proportion of the needle-like structure in the steel plate is reduced, which is not preferred. Therefore, in order to prevent excessive dislocations from being introduced into the steel plate and increase the aspect ratio of the original austenite grains of the annealed steel plate, the rolling rate is limited to less than 20%.

[0189] The method for manufacturing a steel sheet of this embodiment allows omitting cold rolling, that is, setting the cold rolling rate to 0%. However, cold rolling can promote the precipitation of AlN that contributes to the refinement of the prior austenite grain size, so cold rolling may be performed at a reduction rate of 20% or less.

[0190] When pickling is performed before cold rolling, it may be performed by a known method.

[0191] <Annealing process>

[0192] In the annealing step, the steel sheet after the coiling step or the cold rolling step is heated to an annealing temperature of Ac3 point to 900° C. in an atmosphere with an oxygen potential of −1.50 or higher, and is maintained at the annealing temperature for 10 seconds to 600 seconds.

[0193] If the annealing temperature is lower than the Ac3 point or the holding time at the annealing temperature is less than 10 seconds, the γ phase transformation becomes insufficient and the preferred metal structure cannot be obtained in the end. In addition, the precipitation of AlN used to refine the metal structure also becomes insufficient. On the other hand, when the annealing temperature exceeds 900°C, the austenite grains coarsen. In addition, when the holding time at the annealing temperature exceeds 600 seconds, the austenite grains coarsen and the productivity decreases.

[0194] Furthermore, in the annealing step, decarburization in the surface region is promoted, and the metal structure in the surface region of the finally obtained steel sheet is made softer than that at the t / 4 position.

[0195] When the oxygen potential of the heating atmosphere is lower than -1.50, decarburization of the surface layer region becomes insufficient. The oxygen potential of the atmosphere in which the steel sheet is heated refers to the partial pressure P of water vapor in the atmosphere. H2O Divided by the hydrogen partial pressure P H2 The common logarithm of the obtained value, log 10 (P H2O / P H2 ). The oxygen potential in the annealing step is, for example, -0.01 or less.

[0196] The metal structure in the surface region tends to become coarse by promoting decarburization, but the metal structure in the surface region can be refined by precipitating AlN, and the diameter of the prior austenite grains in the plate thickness direction can be set to 10.0 μm or less as described above.

[0197] <First Cooling Step>

[0198] In the first cooling step, the steel sheet after the annealing step is cooled to a first temperature range of (Ms point-100° C.) to Bs point at an average cooling rate of 20° C. / sec or more.

[0199] If the average cooling rate is lower than 20°C / sec or the cooling stop temperature exceeds the Bs point, ferrite, pearlite, etc. are excessively generated during or after cooling, and the target metal structure cannot be obtained. The average cooling rate in the first cooling step is, for example, 200°C / sec or lower.

[0200] Furthermore, if the cooling stop temperature is lower than Ms point - 100°C, the holding step of the next step cannot be performed, or even if the material can be reheated and held in the first temperature range, excessive martensite will be formed when cooling is stopped, and ultimately the specified amount of retained austenite cannot be ensured.

[0201] <Maintaining process>

[0202] In the holding step, the temperature of the steel sheet is held in a first temperature range of (Ms point - 100°C) to Bs point for 60 seconds to 600 seconds.

[0203] This temperature range is a temperature range in which bainite is generated, and therefore, by maintaining the temperature in this temperature range, bainite transformation occurs in the surface layer region.

[0204] When the holding time is less than 60 seconds, a sufficient bainite volume fraction cannot be obtained. On the other hand, when the holding time exceeds 600 seconds, bainite transformation occurs even at the t / 4 position, and the target metal structure cannot be obtained.

[0205] In the present embodiment, the term "maintaining" means that the steel sheet temperature is within the range of (Ms point - 100°C) to Bs point, which means that the temperature may be changed as long as it is within the temperature range.

[0206] In the case of plating (forming a coating), the steel sheet is immersed in a hot-dip galvanizing bath. In addition, the hot-dip galvanized steel sheet may be alloyed to form an alloyed hot-dip galvanized steel sheet. In this case, the temperature of the steel sheet can be maintained by using the heat applied to the steel sheet during hot-dip galvanizing and alloying. The conditions can be known conditions.

[0207] <Second Cooling Step>

[0208] In the second cooling step, the steel sheet after the holding step is cooled to a second temperature range of 250° C. to 150° C. at an average cooling rate of 20° C. / sec or more.

[0209] This cooling causes the untransformed austenite to transform (a portion of the stable austenite remains as retained austenite). If the average cooling rate is lower than 20°C / sec or the cooling stop temperature exceeds 250°C, the volume fraction of the metal structure other than the tempered martensite at the t / 4 position becomes excessive, and the target metal structure cannot be obtained. The average cooling rate in the second cooling step is, for example, 200°C / sec or less.

[0210] Example

[0211] Slabs having the chemical compositions shown in Tables 1-1 to 1-4 were produced by continuous casting.

[0212] The slabs were heated to the heating temperatures shown in Tables 2-1 and 2-2, and hot rolled to produce 2.8 mm hot rolled steel sheets so that the finishing temperature of the finish rolling reached the temperatures shown in Tables 2-1 and 2-2. However, since cracks occurred in the slabs of No. 38 and No. 42, no further tests were performed.

[0213] The hot-rolled steel sheets after hot rolling were cooled to the coiling temperature at the average cooling rate shown in Table 2-1 and Table 2-2, coiled at the coiling temperature, and cooled to room temperature.

[0214] After that, the coiled hot-rolled steel sheets were uncoiled, and some of them were pickled and then cold-rolled at the cumulative reduction ratios shown in Tables 2-1 and 2-2 to produce cold-rolled steel sheets with a thickness of 2.2 to 2.8 mm. (The examples with the cumulative reduction ratio "-" were not cold-rolled.)

[0215] Then, the steel sheets (cold rolled steel sheets if cold rolled, hot rolled steel sheets if not cold rolled) were annealed under the conditions of Tables 2-1 and 2-2. At this time, the holding time at the heating temperature (annealing temperature) was set to 10 seconds to 600 seconds.

[0216] After that, the first cooling, holding, and second cooling are performed under the conditions of Table 3-1 to Table 3-2. At this time, for a part of the steel sheet, during the holding, it is immersed in a molten zinc bath to make a hot-dip galvanized steel sheet. In addition, for a part of the hot-dip galvanized steel sheet, alloying treatment is performed to make an alloyed hot-dip galvanized steel sheet. The holding time in the table is the time including the immersion in the hot-dip galvanizing bath and the time to reach the specified temperature through the alloying treatment. In addition, the cooling stop temperature of the second cooling is set to 150°C to 250°C.

[0217] Ms point (°C) and Bs point (°C) are obtained using the following formulas based on the chemical composition of the slab. At this time, regarding Sα, a steel plate having the same temperature history is prepared in advance, and the area ratio of ferrite in the center of the steel plate is obtained and used.

[0218] Ms=541-474×[C] / (1-Sα / 100)-15×[Si]-35×[Mn]-17×[Cr]-17×[Ni]+19×[Al]

[0219] Bs=820-290×[C] / (1-Sα)-37×[Si]-90×[Mn]-65×[Cr]-50×[Ni]+70×[Al]

[0220] For the structure of the t / 4 position of the base steel plate and the structure of the surface area of ​​the obtained steel plate (hot-rolled steel plate, cold-rolled steel plate, hot-dip galvanized steel plate, alloyed hot-dip galvanized steel plate), the above-mentioned method is used to measure the fraction (volume ratio) of each phase and the diameter of the original austenite grains in the thickness direction of the plate.

[0221] The results are shown in Tables 4-1 and 4-2.

[0222] Furthermore, the tensile strength (TS), bendability, and low-temperature LME resistance of the obtained steel sheets were evaluated in the following manner. The results are shown in Tables 5-1 and 5-2.

[0223] [Tensile Strength (TS)]

[0224] The value can be obtained by taking a JIS No. 5 tensile test piece from the steel plate in a direction perpendicular to the rolling direction and performing a tensile test in accordance with JIS Z2241:2011.

[0225] If the tensile strength is 1470 MPa or more, it is judged that the steel sheet has the desired strength.

[0226] [Flexibility]

[0227] The bending test was carried out according to VDA standard VDA238-100 to find the maximum bending angle.

[0228] When the maximum bending angle is 90 degrees or more, it is judged that the bendability is excellent.

[0229] [LME resistance to low temperature]

[0230] A servomotor pressurized single-phase AC spot welder (current frequency 50 Hz) was used to continuously perform welding with the pressurization set to 400 kgf and the current value changed to 11 kA, 9 kA, or 13 kA, and a cross section passing through the center of the nugget was observed at a magnification of 50 times using an optical microscope.

[0231] As a result of the observation, when cracking was not observed in the shoulder portion, it was judged that the low-temperature LME resistance was excellent.

[0232] [Table 1-1]

[0233]

[0234] [Table 1-2]

[0235]

[0236] [Table 1-3]

[0237]

[0238] [Table 1-4]

[0239]

[0240] [Table 2-1]

[0241]

[0242] [Table 2-2]

[0243]

[0244] [Table 3-1]

[0245]

[0246] [Table 3-2]

[0247]

[0248] [Table 4-1]

[0249]

[0250] [Table 4-2]

[0251]

[0252] [Table 5-1]

[0253]

[0254] [Table 5-2]

[0255]

[0256] As can be seen from Tables 1-1 to 5-2, with respect to the inventive examples, the preferred manufacturing conditions allow the chemical composition, the metal structure at the t / 4 position and the surface region, and the diameter of the original austenite grains in the thickness direction of the plate to be within the scope of the present invention. As a result, the steel has a high strength of more than 1470 MPa and excellent bendability and low-temperature LME resistance.

[0257] In contrast, in the comparative examples, at least one of the chemical composition, the metal structure at the t / 4 position and the surface area, and the diameter of the original austenite grains in the plate thickness direction is outside the scope of the present invention, and at least one of the tensile strength, bendability, and low-temperature LME resistance does not meet the target.

[0258] Industrial Applicability

[0259] According to the present invention, a steel sheet having sufficient ductility, bendability and LME properties applicable to press forming and the like and a method for manufacturing the steel sheet can be obtained. The present invention contributes to the development of industries that can contribute to solving global environmental problems by reducing the weight of automobile bodies.

Claims

1. A steel plate, characterized in that: have: parent steel plate; and The zinc plating layer formed on the surface of the base steel plate, The base steel plate has the following chemical composition: in terms of mass %, it contains: C: 0.180% to 0.400%, Si: 0.050% to 1.000%, Mn: 2.00% to 4.00%, Al:0.10%~2.00%、 Ti: 0.010% to 0.200%, B:0.0010%~0.0100%、 N:0.0010%~0.0100%、 P:0%~0.0400%、 S:0%~0.0100%、 O:0%~0.0060%、 Cr:0%~0.50%、 Ni: 0% to 1.00%, Cu: 0% to 1.00%, Mo: 0% to 0.500%, Nb: 0% to 0.200%, V:0%~0.500%、 W:0%~0.100%、 Ta: 0%~0.100%, Sn: 0% to 0.050%, Co: 0% to 0.500%, As: 0%~0.050%, Sb: 0% to 0.050%, Mg: 0% to 0.050%, Ca: 0% to 0.040%, REM: 0%~0.050%, Zr:0%~0.050%、 Bi: 0% to 0.050%, Sr: 0% to 0.050%, and The rest: Fe and impurities, When the plate thickness of the base steel plate is set to t, the metal structure at the position t / 4, which is t / 4 away from the surface in the plate thickness direction cross section of the base steel plate, includes, by volume percentage: Tempered martensite: more than 85%, Retained austenite: more than 7%, One or more selected from ferrite, pearlite, bainite, and fresh martensite: 0% to 8%, The metal structure in the range from the surface to the position of 50μm in the cross-section in the thickness direction of the plate, i.e., the surface area, contains more than 30% bainite by volume, and the remainder is one or more selected from ferrite, pearlite, tempered martensite, primary martensite and retained austenite. In the surface area, the diameter of the original austenite grains in the thickness direction of the plate is less than 10.0μm, and the tensile strength of the steel plate is more than 1470MPa.

2. The steel plate according to claim 1, characterized in that: When the Al content in atomic % is set to "Al", the N content is set to "N", and the Ti content is set to "Ti", the formula (1) is satisfied, 《Al》≥《N》-0.5×《Ti》 (1).

3. The steel plate according to claim 1 or 2, characterized in that: The zinc coating is a hot-dip galvanized coating.

4. The steel plate according to claim 1 or 2, characterized in that: The zinc coating is an alloyed hot-dip galvanized layer.

5. A method for manufacturing a steel plate, characterized in that: The process has the following steps: a heating step of heating the slab in such a manner that a heating temperature T in K satisfies the formula (2) when the Al content in mass % is set to [Al] and the N content is set to [N]; A hot rolling step of hot rolling the slab after the heating step to obtain a steel plate; A coiling step of cooling the steel plate at an average cooling rate of 20°C / s or more to a coiling temperature of 500°C or less, and coiling the steel plate at the coiling temperature; A cold rolling step, wherein the steel sheet after the coiling step is pickled as required and then cold rolled at a cumulative reduction rate of 20% or less; An annealing step, wherein the steel sheet is heated to an annealing temperature of Ac3 point to 900° C. in an atmosphere having an oxygen potential of -1.50 or higher, and maintained at the annealing temperature for 10 seconds to 600 seconds; A first cooling step of cooling the steel sheet after the annealing step to a first temperature range of Ms point - 100°C to Bs point at an average cooling rate of 20°C / sec or more; A step of maintaining the temperature in the first temperature range for 60 seconds to 600 seconds; and a second cooling step of cooling the steel plate after the holding step to a second temperature range of 250° C. to 150° C. at an average cooling rate of 20° C. / sec or more, log 10 ([Al]×[N])≤-9730 / T+3.36 (2)。

Citation Information

Patent Citations

  • Information processing device, monitoring program, and monitoring method

    JP2022143631A

  • High-strength plated steel sheet having excellent plating properties, workability, and delayed fracture resistance, and method for producing same

    WO2016111275A1

  • Steel sheet and manufacturing method therefor

    WO2021251276A1